2012
DOI: 10.1111/j.1742-481x.2012.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an ultra‐lightweight, single‐patient‐use negative pressure wound therapy system over dermal regeneration template and skin grafts

Abstract: As the use of negative pressure wound therapy (NPWT) over skin grafts has increased, traditional methods of NPWT system reimbursement and application are increasingly being challenged. A simplified method of accessing and operating NPWT in the outpatient setting is needed, particularly in cases where immediate outpatient use of NPWT is optimal. We evaluated use of a new ultra-lightweight, off-the-shelf, disposable, single-patient-use NPWT system (SP-NPWT; V.A.C.Via™ Therapy, KCI USA, Inc., San Antonio, TX) ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Results showed that all grafts took successfully and had similar graft take rates compared to current graft take rates with NPWT/ROCF (5,9). More importantly, the SP‐NPWT device allowed for discharge of patients on the same day of DRT or graft placement (12).…”
Section: Use Of Npwt/rocf With Skin Graftsmentioning
confidence: 78%
See 2 more Smart Citations
“…Results showed that all grafts took successfully and had similar graft take rates compared to current graft take rates with NPWT/ROCF (5,9). More importantly, the SP‐NPWT device allowed for discharge of patients on the same day of DRT or graft placement (12).…”
Section: Use Of Npwt/rocf With Skin Graftsmentioning
confidence: 78%
“…As there are now ultra‐lightweight, disposable, single‐patient‐use NPWT systems (SP‐NPWT; V.A.C.Via™ Therapy System, KCI USA, Inc., San Antonio, TX) available, an important benefit of using NPWT/ROCF in graft patients relates to the ability to perform grafts as outpatient procedures or to discharge postoperative patients earlier. A pilot study by Gabriel et al (12) evaluated the use of SP‐NPWT over skin grafts and dermal regeneration templates (DRTs). Thirty‐eight patients with 41 wounds received SP‐NPWT over STSGs, full‐thickness skin grafts (FTSGs) and DRTs.…”
Section: Use Of Npwt/rocf With Skin Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…HE in the reviewed articles was present as a passing mention and related to three purposes: justifying an aspect of the research design, 23,24,[26][27][28][29][30]53 defending unexpected findings, [32][33][34][35][36][38][39][40]44,46,54,55 and acknowledging a deficit of conducting an open-label study. 37,42,47,56,57 Regardless of the purpose, the term HE was referred to briefly and lacked definition in most of the reviewed articles.…”
Section: The Mentioning Of He In Passingmentioning
confidence: 99%
“… 15 16 Over the past several years, several miniaturized, disposable, single-patient NPWT (SP-NPWT) devices have been introduced. 5 6 17 18 19 20 21 These devices have the potential to simplify wound care in the management of skin graft donor sites in the outpatient setting. The authors describe a series of 10 patients with STSG donor site wounds treated with an off-the-shelf, miniaturized, SP-NPWT device.…”
mentioning
confidence: 99%